2016
DOI: 10.1515/bhk-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Leg stiffness and potential energy in the countermovement phase and the CMJ jump height

Abstract: SummaryStudy aim: The elastic potential energy accumulated in the musculotendinous units during the countermovement phase of a jump adds up to the energy supplied by the contracting muscles used in the take-off phase. Consequently, the total mechanical energy used during the jump may reach higher values. Stiffness represents a quantitative measure of a body's elastic properties. Therefore, the aim of this study was to establish the relationship between leg stiffness and the countermovement jump height. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…The speculations concerning a desirable value “leg-spring” stiffness that is the most advantageous for the accumulation of potential elastic energy and most favours reaching maximal sport performance have already been addressed in many previous studies [ 1 , 3 , 22 , 24 – 28 , 31 35 ]. However, no studies have provided unequivocal evidence for the presence of a desired “leg-spring” stiffness value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The speculations concerning a desirable value “leg-spring” stiffness that is the most advantageous for the accumulation of potential elastic energy and most favours reaching maximal sport performance have already been addressed in many previous studies [ 1 , 3 , 22 , 24 – 28 , 31 35 ]. However, no studies have provided unequivocal evidence for the presence of a desired “leg-spring” stiffness value.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this may be the lack of longitudinal studies that have investigated the effects of strength or power training on mechanical stiffness and consequently the relative lack of concrete recommendations that would allow to improve the speed-strength abilities of an athlete and their competitive sport results. The speculations concerning a desirable value of “leg-spring” stiffness that is the most advantageous for the accumulation of potential elastic energy and most favours reaching maximal sport performance have been partially examined [ 1 , 3 , 22 , 24 – 28 , 31 35 ]. However, no studies have provided unequivocal evidence for the presence of a desired value of “leg-spring” stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…The acceptable reliability of the RSI modified is in line with the findings of previous studies [ 18 , 20 , 33 ] (CV ≤ 10%). The only performance variable that presented a questionable reliability was the leg stiffness (CV = 11%), a variable that is considered as a quantitative measure of the elastic properties of lower body muscles [ 9 ]. Although several studies reported similar findings [ 17 , 19 , 34 ], Heishman et al [ 21 ] argued that leg stiffness cannot be considered a reliable CMJ-derived variable because they obtained CV values that exceeded 20%.…”
Section: Discussionmentioning
confidence: 99%
“…One variable that stands out from all performance metrics is jump height, due to its direct association with the performance on a variety of sport-specific tasks and physical preparedness of the athletes [ 3 , 8 ]. Moreover, some complex metrics, such as leg stiffness (i.e., ratio of vertical ground reaction force to minimal centre of mass displacement) and modified reactive strength index (RSI modified; i.e., quotient of jump height and push-off duration), are gaining massive popularity in terms of being considered as indirect measures of elastic/reactive properties of lower body muscles [ 9 , 10 , 11 ]. Kinetic variables (e.g., mean force, peak force, impulse) have been frequently computed by sports scientists and practitioners due to their ability to provide in-depth insight into the mechanics of the CMJ execution [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…There were decreases in both power output and jump velocity after the completion of the selection course, these were not deemed to be significant. Interestingly and unexpectedly, vertical jump increased by 23.1% over the selection course, potentially due to an increase in passive stiffness, and decrease in active stiffness in the lower limb and consequent increased ability to store elastic potential energy [ 23 ]. Evidence of this ability to redirect energy through the hysteresis loop may be highlighted by the increases in joint stiffness as measured by the sit-and-reach assessment.…”
Section: Discussionmentioning
confidence: 99%